Marginal bone level in two Danish cross-sectional population samples in 1997–1998 and 2007–2008. (4th July 2018) - Bahrami, Golnosh; Vaeth, Michael; Wenzel, Ann; Isidor, Flemming
Abstract: Objective: The aim of this study was to compare the marginal bone level of two randomly selected population samples from 1997/1998 and 2007/2008, with special emphasis on the role of smoking habits and gender. Materials and methods: Two cross-sectional randomly selected population samples [1997/1998 ( N  = 616) and 2007/2008 ( N  = 396)] were analysed with respect to the marginal bone level. The marginal bone level was measured in full-mouth intraoral radiographs. Information on smoking was gathered using questionnaires. Multiple regression analysis was used in order to adjust for correlating factors (gender, age, smoking habits and number of teeth). Results: After adjusting for confounding factors, the population sample from 2007/2008 had on average a slightly, but statistically significantly, more reduced average marginal bone level (0.15 mm) than the population sample from 1997/1998. Men had more reduced marginal bone level than women (0.12 mm). Smokers in both population samples had more reduced marginal bone level than non-smokers (0.39 mm and 0.12 mm for 1997/1998; 0.65 mm and 0.16 mm for 2007/2008). Conclusions: In these populations, sampled 10 years apart, the 2007/2008 population sample had a slightly more reduced marginal bone level than the 1997/1998 population sample. Men had more reduced marginal bone level than women, and smoking is considered a major risk factor for a reduced marginal bone level.